The impact of exercise intervention on social interaction in children with autism: a network meta-analysis - Hou, Yaoqi; Song, Zhuo; Deng, Jiaqi; Song, Xiangqin (Frontiers in Public Health, 2024)
Background：Extensive research has documented the positive impacts of physical activity on children and adolescents with Autism Spectrum Disorders (ASD). However, the specific benefits of various sports on the social functioning of children with ASD remain ambiguous. This study aims to employ a network meta-analysis to investigate the effects of different sports on the social functioning of children and adolescents with ASD and to establish a ranking of their effectiveness.Methods: This study conducted a comprehensive online search across Web of Science, PubMed, Cochrane, and Embase databases for randomized controlled trials and quasi-experimental studies focusing on social functioning outcomes. Data were synthesized using a Bayesian framework.Results: Sixteen relevant studies encompassing 560 participants were included. According to Cohen's classification, minibasketball (SMD = 0.84, 95% CI: 0.46, 1.20), SPARK (SMD = 0.88, 95% CI: 0.06, 1.70), and Karate (SMD = 1.10, 95% CI: 0.27, 2.00) demonstrated high effect sizes, with Karate identified as the most effective intervention. Conversely, Combined Exercise and Nei Yang Gong interventions exhibited the least significant effects, falling below small effect sizes.ASD to varying extents, with Karate emerging as the most efficacious.